Designing a web log book _HIS system for the school of dentistry, Tehran university of medical sciences - Reza Sharifi; Mohammad Bayat; Sheida Kordi; Afshin Heidari; Sadat Hasheminasab (Tehran University of Medical Sciences, 2021)
Background and Aims: This study aimed to collect reports and HIS in a web-based system due to the problems of paper recording of student activities in practical courses, as well as the lack of computers in the departments for observing graphs and treatment plans. Materials and Methods: The initial graphic design of the website was done after the assessment of needs and the necessary planning for designing the website. The main template of the website was designed after consulting with the faculty and the designer company. A combination of HTML, CSS, JQuery, and Java script was used for static coding and what the user sees or interacts with. Then, the basic information entered the website and the content designer put the website in the designed layout. In the end, a sample hosting space was prepared and the website was fully provided to the professors and faculty officials to work with as an administrator and a user. They conveyed all their opinions and the corrections were made based on the feedback given. Results: The use of the internet and software with a central database played a significant role in monitoring and evaluating the long-term information of the student and the evaluation of the entire department, universities, and patients in each region up to macro-national evaluations. This could give the expansion and advancement of science in addition to the central registration of documents and radiographs, as well as their ease to access. Conclusion: The designed website was well received among the students and the attending staff. Introducing a web based logbook and HIS system can optimize the clinical teaching. These logbooks could help both students and staff saving time and resources, and to facilitate providing better personalized care for patients.